Effects of side groups on the kinetics of charge carrier recombination in dye molecule-doped multilayer organic light-emitting diodes. Issue 1 (19th November 2014) - Shi, Shengwei; Gao, Feng; Sun, Zhengyi; Zhan, Yiqiang; Fahlman, Mats; Ma, Dongge
Abstract : Effects of side groups on the kinetics of charge carrier recombination are investigated in dye molecule-doped multilayer organic light-emitting diodes by transient electroluminescence. Abstract : The carrier recombination coefficient ( γ ) in dye molecule-doped multilayer organic light-emitting diodes was quantified by transient electroluminescence. It was found that γ and device efficiency were both strongly dependent on the molecular structures of the dopants.